Distribution and clinical significance of blood dendritic cells in children with juvenile idiopathic arthritis. Issue 6 (26th October 2007) - Smolewska, E; Stańczyk, J; Brózik, H; Biernacka-Zielińska, M; Cebula, B; Robak, T; Smolewski, P
Abstract : Background: A role for dendritic cells (DC) in the development of adult rheumatoid arthritis has been suggested. To date, this problem has been poorly explored in juvenile idiopathic arthritis (JIA). Objective: To analyse distribution and maturation status of blood DC (BDC) in JIA. Methods: Absolute BDC counts were assessed by the "single platform" method in peripheral blood (PB) of 47 untreated children with JIA and 32 healthy controls. Moreover, BDC were investigated in JIA synovial fluid (SF). When the panel of monoclonal antibodies against BDC antigens (BDCA) was used, three BDC subpopulations were determined: myeloid type 1 (mDC1; BDCA-1+/HLA-DR+/CD19−), myeloid type 2 (mDC2; BDCA-3+/HLA-DR+/CD14−) and plasmacytoid (pDC; BDCA-2+/HLA-DR+/CD123+). Results: A considerable deficiency of all subtypes of BDC was found in the PB of children with JIA. BDC counts in JIA SF were significantly higher than in PB both from children with JIA (p<0.001) and healthy children (p<0.001). SF BDC, especially mDC1 and mDC2 subtypes, had significantly higher expression of maturation markers (CD40, CD80, CD86 or CD83 antigens) than those from PB. A smaller number of PB BDC at diagnosis correlated significantly with poor response to treatment. Conclusions: A deficiency of BDC in PB is accompanied by enrichment of SF with those cells. Probably, circulating BDC migrate to joints where they undergo maturation and help to mediate and maintain the local immune response. Interestingly, the level of PD BDC deficiency seems to influence the outcome in children with JIA.